Does the Angulation of an Impacted Mandibular third Molar Affect the Prevalence of Preoperative Pathoses? - Ahmet Altan; Nihat Akbulut (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: The removal of a third molar tooth associated with a pathological condition is usually an easy decision. However, it is necessary for clinicians to know about the prevalence of preoperative pathologies associated with impacted mandibular third molars to the identification of the prophylactic approach to be applied to symptom-free impacted third molars. Purpose: The objective was to investigate the effect of the angulation of impacted mandibular third molars on the prevalence of associated pathologies. Materials and Method: In this retrospective study, we examined the panoramic radiographs of 954 patients referred for impacted third molar surgery. A total of 1598 impacted mandibular third molar teeth were included in the study. Pathological conditions included the caries on distal surface of the adjacent second molar, caries on impacted mandibular third molars, bone loss distal to the adjacent second molar, the radiolucent area distal to the impacted mandibular third molar were determined. Results: Caries were observed more in the impacted third molar (18.9%) compared to the adjacent second molar (15.8%). The radiolucent area on distal surface of the impacted mandibular molar was 11%, while the periodontal bone loss distal to the adjacent second molar was 4.9%. Mesioangular-impacted mandibular third molars had high risk of caries development on second and third molar. The prevalence of periodontal tissue damage to the adjacent second molar was higher in horizontal and mesioangular angulation. Vertical and distoangular-impacted mandibular third molars had high risk for bone loss at distal aspect. Conclusion: The prevalence rate of pathological conditions in mesioangular impacted teeth was higher.